The Effect of Online Shopping Preference on Social Media and Webstore to Purchase Decision of Start-Up Company - Pohan, Atika Sari; Rachmawati, Evy (Journal of Innovation, Business and Entrepreneurship, 2016)
Abstract. lPipel is a fashion company which offer woman bag multiwear that delivered the concept of two-tone in every article. The company focus to increase marketing strategy by using two startegies, namely webstore and social media. Start-up company can build online business using any media such as social media and webstore. Nowadays, most of the owner business online choose social media as online transaction. Furthermore, it can be promotion tools. On other hand, issues being faced by e-commerce are less content, apperance photo of product, also product description. It can be concluded that the business owner havent effective while use it. There are 3 variables to be examined namely quality, product, and trust. Each variables tested toward social media and webstore. This study to find out which variable is driving consumers to purchase decision online whether through social media or webstore. The method to be used is quantitative and qualitative (mix method). Data will be obtained by interviewing 129 respondents via the enclosed questionnaire. In addition, the interview will also be made to obtain qualitative data that able help in the analysis process. The result of social media showed that the only one variable that has significant influence which is quality.Â Then, the result ofÂ webstore showed that there are two variables that has significant influence are quality and trust. In this case, the most influence variable falls to quality on webstore and social media. The last analysis, the result show social media has the higher mean rank than webstore.Â Keywords: social media, websites, online shopping, purchase decision.